Structural complexity and primary production resistance are coupled in a temperate forest - Niedermaier, Kerstin M.; Atkins, Jeff W.; Grigri, Maxim S.; Bond-Lamberty, Ben; Gough, Christopher M. (Frontiers in Forests and Global Change, 2022)
The capacity of forests to resist structural change and retain material legacies–the biotic and abiotic resources that persist through disturbance–is crucial to sustaining ecosystem functioning after disturbance. However, the role of forest structure as both a material legacy and feature supporting carbon (C) cycling stability following disturbance has not been widely investigated. We used a large-scale disturbance manipulation to ask whether legacies of lidar-derived canopy structures drive 3-year primary production responses to disturbance. As part of the Forest Resilience Threshold Experiment (FoRTE) in northern Michigan, USA we simulated phloem-disrupting disturbances at a range of severities and two disturbance types. We quantified the legacies of forest structure using two approaches: one measuring change in structure and primary production from pre- to post-disturbance and the second estimating resistance as log transformed ratios of control and treatment values. We found that total aboveground wood net primary production (ANPPw) was similar across disturbance severities as legacy trees rapidly increased rates of primary production. Experiment-wide, disturbance had limited effects on change in mean structural complexity values; however, high variance underscored large differences in the magnitude and direction of complexity’s response at the plot-scale. Plot-scale structural complexity, but not vegetation area index (VAI), resistance strongly predicted ANPPw resistance while temporal VAI and structural complexity changes did not. We conclude that the presence of material legacies in the form of forest structure may affect primary production stability following disturbance and that how legacies are quantified may affect the interpretation of disturbance response.